CHARACTERIZATION AND ANTIBIOTIC PROFILES OF LACTIC ACID BACTERIA ISOLATED FROM "TCHOUKOU" TRADITIONAL MILK CHEESES PRODUCED IN THE ZINDER REGION OF NIGER REPUBLIC, WEST AFRICA - Rabiou, Mahamadou; Owino, Willis; Mbogo, Kevin (International Journal of Food Sciences, 2021)
Purpose: The current study's aim is to identify Lactic Acid Bacteria (LAB) isolated from " Tchoukou" cheeses made using cow, camel, and goat milk sampled from Zinder region of Niger Republic. Methodology: Nine samples were collected aseptically from cheesemakers in Zinder Region and the isolation of LAB isolates was carried out using selective media. The isolates were identified based on their phenotypic, biochemical and genotypic characteristics. Findings: A total of 13 strains of Lactic Acid Bacteria (LAB) were isolated and morphologically and biochemically characterized. Cell morphology analysis identified 12 isolates as rods shaped while 1 isolate was cocci. All isolates were gram positive, Triple Sugar Ion Agar tests (TSIA) positive, and tested negative for catalase. The isolates were also found to be able to grow in a temperature range between 15 and 45 C.. The isolates' 16S rRNA gene was amplified using bacterial universal primers 27F and 1492R. Based on 16S rRNA gene analyses, the 13 LAB isolates were grouped into the genera Lactobacillus, and Weissella, traditionally known to occur in raw milk and milk products. The genus Lactobacillus was dominant with 76.92% of the LAB isolated. Most of the isolated strains were susceptible to eight antibiotics. Therefore, 5 (38.46%), 3(23.08%), and 4 (30.77%) isolates showed resistance respectively against Kanamycin, Streptomycin, and Co-Trimoxazole. One same isolate (7.69%) was discovered resistant to Sulphamethoxazole and Ampicillin. Unique contribution to theory, practice and policy: this study was performed to characterize the LAB isolates found in homemade cheeses that could serve as the potential source for the industries and commercial applications.